Protein Profile of Mozzarella Cheese Produced with Treatment of Coagulation and Stretching Temperature Combination - Purwadi Purwadi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
A research used lime juice as acidifier in the making of Mozzarella cheese was aimed to learn the protein profile produced with treatment of coagulation stretching temperature combination. The method used in this research was factorial experiment of 4 x 4, the first factor was coagulation temperature (G) : G1 = 30 oC, G2 = 35 oC, G3 = 40 oC, and G4 = 45 oC, and the second factor was stretching temperature (M) : M1 = 70 oC, M2 = 75 oC, M3 = 80 oC, and M4 = 85oC. Combination of coagulation temperature 30 and 35oC with different stretching temperatures 70, 75, 80, and 85 oC, gave the same protein electroforegram, but the combination of coagulation temperature 30 and 35 oC and coagulation temperatur 40 and 45 oC with different stretching temperature gave different protein electroforegram. From this experiment, its could be concluded that the treatment of coagulation temperature 30 oC with stretching temperature 75 oC is the best treatment. Keywords: protein profile, Mozzarella cheese, coagulation temperature, stretching temperature